Biodefense vaccines - Nataro, James (Henry Stewart Talks, 2009)
Category A threats, Available vaccines, Smallpox, Vaccinia: the first vaccine, Vaccination has risks, Anthrax, Vaccines in advanced trials, Plague as an agent of bioattack, Response to biodefense needs, Yersinia pestis pathogenesis, The F1 capsule, Type III secretion system, Immunity to Y. pestis, Plague vaccines, Disadvantages of the current approaches, New plague vaccine approaches, Subunit vaccines, Prime-boost strategies, Innovative approaches to vaccine delivery may provide practical, highly effective protective interventions
Reviewed at 2016/11/18